Attributes of Effective Online Promotion Strategies: Case Study of European Universities - Bularca, Maria Cristina; Coman, Claudiu; Nechita, Florin; Briciu Victor-Alexandru (Springer, 2024)
Living in the age of technology, universities are in need of keeping up with the development of the means of communication and the way new generations of students use these means. The purpose of the research was to identify the online promotion strategies used by the best European universities that provide master programs in communication based on a top made by Times Higher Education, in order to create an online promotion and communication procedure for Transilvania University of Brasov and other universities. Firstly, we analyzed the way the first 20 European universities with master programs in communication, according to a top made by The Times Higher Education, promote themselves online. Secondly, in order to be able to make a comparison and break down rules of good practice we analyzed the online promotion of 5 universities that occupy lower positions in the top. The universities were analyzed based on an adapted content grid with 29 criteria, including: contact information, real time assistance, social media instruments, infor-mation about: study programs, campus, employees, admission. Our results showed that the best European universities offering masters programs in communication, use various integrated online promotion and communication strategies and utilize combinations of tools that match their profile. Therefore, while there are similari-ties between the strategies used by the best European universities and the European universities with lower positions in the top, strategies of the best ranked univer-sities and their promotion and communication methods can be adapted and used by other universities in order to improve their procedure of online promotion and communication.